Building digital libraries a how-to-do-it manual - Reese, Terry Jr (How-to-do-it manuals for librarians, 2019)
Whether you're embarking on the challenge of building a digital collection from scratch, or simply need to understand the conceptual and technical challenges of constructing a digital library, this top-to-bottom resource is the ideal guidebook to keep at your side, especially in this thoroughly updated and reworked edition